2015
DOI: 10.4103/1119-3077.163275
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported physical activity among health care professionals in South-West Nigeria

Abstract: Majority of the HCPs had inadequate PA levels according to WHO guidelines. BMI≥25 kg/m2 was associated with inadequate physical inactivity. The low level of PA implies that these HCPs are at risk for NCDs. This will have a negative impact on availability of human resource for health. There is an urgent need to establish programs to increase PA among HCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 1 publication
4
23
4
2
Order By: Relevance
“…A health care worker who is with BMI less than 25 Kg/m 2 were almost five times more likely to engage in physical activity compared with whose BMI ≥25 Kg/m 2 . This finding is in line with a study done in Nigeria [32]. On the contrary, a study done among health care workers in Malaysia [14], level of BMI had no association with physical activity level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A health care worker who is with BMI less than 25 Kg/m 2 were almost five times more likely to engage in physical activity compared with whose BMI ≥25 Kg/m 2 . This finding is in line with a study done in Nigeria [32]. On the contrary, a study done among health care workers in Malaysia [14], level of BMI had no association with physical activity level.…”
Section: Discussionsupporting
confidence: 91%
“…The current study result was higher than a study in Malaysia, 67.2 % (23), Brazil 72.5% (26) and, Nigeria 20.8 % [16]. This inconsistency might be due to a difference in physical activity measurement tools used along with variation in the study population.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…This is incongruent with the prevalence of sedentary lifestyle among bank employees in Belgaum city (44%) and among bankers in Ilorin metropolis (29.6%) (8,9) its also lower than the prevalence of sedentary lifestyle among health workers in South-west Nigeria (79.2%) (11). Similar definition of sedentary lifestyle was used in their own study in which sedentary people refer to those who do not engage in regular moderatevigorous physical activity (11).…”
Section: Discussionmentioning
confidence: 46%
“…Sedentary behavior and level of physical activity of 425 university population in Flores, Argentina was studied using the self reporting global physical activity questionnaire (GPAQ): 31% were found to be sedentary (5). A cross sectional study conducted in South-west Nigeria among health care workers, revealed that only 20.8% of the respondents had adequate physical activity level (11).…”
Section: Introductionmentioning
confidence: 99%